The obstructed jet in Mrk 231. Issue 3 (3rd March 2021) - Wang, Ailing; An, Tao; Jaiswal, Sumit; Mohan, Prashanth; Wang, Yuchan; Baan, Willem A; Zhang, Yingkang; Yang, Xiaolong
ABSTRACT: Mrk 231 is the closest radio-quiet quasar known and one of the most luminous infrared galaxies in the local Universe. It is characterized by the co-existence of a radio jet and powerful multiphase multiscale outflows, making it an ideal laboratory to study active galactic nucleus (AGN) feedback. We analyse the multi-epoch very long baseline interferometry data of Mrk 231 and estimate the jet head advance speed to be ≲0.013  c, suggesting a sub-relativistic jet flow. The jet position angle changes from −113 ○ in the inner parsec to −172 ○ at a projected distance of 25 pc. The jet structure change might result from either a jet bending following the rotation of the circum-nuclear disc or the projection of a helical jet on the plane of the sky. In the large opening angle (∼60 ○ ) cone, the curved jet interacts with the interstellar medium and creates wide-aperture-angle shocks that subsequently dissipate a large portion of the jet power through radiation and contribute to powering the large-scale outflows. The low power and bent structure of the Mrk 231 jet, as well as extensive radiation dissipation, are consistent with the obstruction of the short-length jet by the host galaxy's environment.